Baseline Body Composition in Prepubertal Short Stature Children with Severe and Moderate Growth Hormone Deficiency. (30th August 2016) - Matusik, Pawel; Klesiewicz, Marta; Klos, Karolina; Stasiulewicz, Martyna; Barylak, Aleksandra; Nazarkiewicz, Patrycja; Malecka-Tendera, Ewa
Abstract : Objective. To compare body composition parameters in short children with severe versus moderate and no growth hormone deficiency (GHD). Design and Method. 61 children (40 boys) were studied. Height SDS, BMI Z -score, waist/height ratio (W/HtR), and body composition parameters (BIA) as fat tissue (FAT%), fat-free mass (FFM%), predicted muscle mass (PMM%), and total body water (TBW%) were evaluated. GH secretion in the overnight profile and two stimulation tests and insulin-like growth factor 1 (IGF-1) level were measured. Results. Overall, in 16 (26%) moderate (7.0 > peak GH < 10 ng/mL) and in 11 (18%) severe (GH ≤ 7.0 ng/mL) GHD was diagnosed. In children with sGHD BMI Z -score, W/HtR and FAT% were significantly higher, while FFM%, PMM%, and TBW% were significantly lower versus mGHD and versus noGHD subgroups. No significant differences between mGHD and noGHD were found. There were no differences in height SDS and IGF-1 SDS between evaluated subgroups. Night GH peak level correlated significantly with FAT%, FFM%, PMM%, and TBW%, (p < 0.05 ) in the entire group. Conclusions. Only sGHD is associated with significant impairment of body composition. Body composition analysis may be a useful tool in distinguishing between its severe and moderate form of GHD.